Cell-cycle regulation in embryonic stem cells: centrosomal decisions on self-renewal - Sumbalova Koledova, Zuzana; Krämer, Alwin; Kafkova, Leona Raskova; Divoky, Vladimir (Stem Cells and Development, 2010)
Embryonic stem cells seem to have the intriguing capacity to divide indefinitely while retaining their pluripotency. This self-renewal is accomplished by specialized mechanisms of cell-cycle control. In the last few years, several studies have provided evidence for a direct link between cell-cycle regulation and cell-fate decisions in stem cells. In this review, we discuss the peculiarities of embryonic stem cell-cycle control mechanisms, implicate their involvement in cell-fate decisions, and distinguish centrosomes as important players in the self-renewal versus differentiation roulette.